EVALUASI VALUE PROPOSITION DAN PERCEIVED VALUE APLIKASI E-WALLET MENGGUNAKAN UX HONEYCOMB, UX QUESTIONNAIRE, DAN SYSTEM USABILITY SCALE (STUDI KASUS: OVO, DANA, DAN SHOPEEPAY) - Benedict Hardyanto Harjono; Nina Setiyawati (STKIP PGRI Tulungagung, 2022)
Fintech (Financial Technology) is an innovation in the financial services industry that utilizes technology. In Indonesia, the highest Fintech growth is in the cashless payment section, dominated by e-wallets. Seeing the high growth in the use of e-wallets, application user experience (UX) and usability are part of the crucial components that need to be continuously evaluated and improved. UX is a term used for the interaction users feel in using a product. Usability is a quality attribute that assesses the level of ease of use of the product. This research evaluates the value proposition and perceived value of the OVO, DANA, and ShopeePay e-wallet applications using UX honeycomb, User Experience Questionnaire (UEQ), and System Usability Scale (SUS). The evaluation of the value proposition is based on 7 aspects of UX honeycomb that must be owned by the product so that users get a good experience and evaluation of perceived value using UEQ and SUS metrics. The results of the value proposition analysis show that the OVO application has a useful, usable, desirable, findable, and valuable value of 5. The only credible value in the DANA application gets a 5. While all aspects of the UX Honeycomb of the ShopeePay application, none of them get a value of 5. From the metric, UEQ found all three applications' UX aspects were positive, except for the Novelty OVO aspect, which was neutral. The results of the SUS, the three applications get a grade scale of C, adjective ratings are good and occupy acceptable acceptability ranges. The results of this study indicate that OVO provides the most superior value based on UX Honeycomb. Meanwhile, from the UEQ interpretation, the average user perception is positive on all UX aspects of the three e-wallets. From the SUS interpretation, it was found that the user has received the usability of the three e-wallet applications.